2014
DOI: 10.1002/2014gc005270
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional electrical structure of the crust and upper mantle in Ordos Block and adjacent area: Evidence of regional lithospheric modification

Abstract: Long-period magnetotelluric (MT) data from project SINOPROBE were acquired and modeled, using three-dimensional (3D) MT inversion, to study the electrical structure of Ordos Block, a component of the North China Craton. For the first time, a high-resolution 3D resistivity model of the lithosphere is defined for the region. Contrary to what would be expected for a stable cratonic block, a prominent lithospheric conductive complex is revealed extending from the upper mantle to the mid-to-lower crust beneath the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 75 publications
9
47
0
Order By: Relevance
“…Zhao et al [] interpreted the feature to be related to low temperatures and a relatively depleted geochemical composition. Consistent results from electromagnetic data demonstrate that a zone with low resistivity can be tracked downward to 150 km [see Dong et al , , Figure 5]. The zone of low resistivity moves southward as depth increases, which is in good agreement with that we see in the V p / V s ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [] interpreted the feature to be related to low temperatures and a relatively depleted geochemical composition. Consistent results from electromagnetic data demonstrate that a zone with low resistivity can be tracked downward to 150 km [see Dong et al , , Figure 5]. The zone of low resistivity moves southward as depth increases, which is in good agreement with that we see in the V p / V s ratio.…”
Section: Discussionmentioning
confidence: 99%
“…conductivity domains were imaged beneath the North Anatolian fault (Kaya et al, 2013), the Red River fault system (Pham et al, 1995), and beneath suture zones in Asia and North America (Dong et al, 2014;Meqbel et al, 2014). In contrast, high resistivity is associated with the Great Slave shear zone up to 50 km depth (Yin et al, 2014) and with a Neoproterozoic collisional suture in northeast Brazil .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Previous regional seismic imaging revealed broad high velocities beneath the Ordos block extending to ≥ 200‐km depths (e.g., Jiang et al, ; Lei, ; Zhao et al, ), and receiver function studies indicated that the lithosphere‐asthenosphere boundary (LAB) is ~200 km deep (Chen et al, ), implying the presence of overall thick cratonic SCLM beneath the Ordos block. However, more recent geophysical observations suggest that lithospheric rejuvenation also occurs at the margins of Ordos during the late Cenozoic, resulting in significant intracratonic heterogeneities (Dong et al, ; Guo, Afonso, et al, ; Guo & Chen, , ; Yu & Chen, ). However, it is still unclear to what extent the SCLM of Ordos block is being modified and what is the dynamic mechanism responsible for the rejuvenation.…”
Section: Introductionmentioning
confidence: 99%